Strategi Pemanfaatan Analisis SWOT Terhadap Penyesuaian Kompetensi Lulusan Peserta Didik Di SMK Negeri 2 Kota Jambi - Wardhani, Meitri Gita Kusuma; Yudha, Redi Indra (SJEE (Scientific Journals of Economic Education), 2025)
This research aims to find out the strategy for using SWOT analysis and its implementation in adjusting the competency of graduate students at SMK Negeri 2 Jambi City based on their absorption capacity in the business and industrial world. The research method used in this research is a qualitative method. The results of the research show that the absorption capacity of the business world and the industrial world for graduates of SMKN 2 Jambi City is still relatively low, so in implementing learning activities you must adapt competencies that lead to the characteristics needed by DU/DI to be able to do work satisfactorily in accordance with their field. The characteristics referred to refer to the knowledge and skills that individuals have and that individuals need to enable them to adapt to the demands of the world of work and the industrial world.